Analysis of Financial Performance Using the Value For Money Approach in Sidomulyo Village Boliyohuto District - Hamzah, Fadilah; Hasan, Wahyudin; Bilondatu, Nikma; Junus, Onong (LPPPIPublishing, 2026)
Financial Performance Analysis Using a Value-for-Money Approach in Sidomulyo Village, Boliyohuto District. (Supervised by Wahyudin Hasan as the Main Supervisor and Nikma Bilondatu as a co-supervisor). This study aims to analyze the effectiveness, efficiency, and economy of Sidomulyo Village's financial management by calculating effectiveness, efficiency, and economy ratios. The research method employed a quantitative approach, using the Village Budget Realization and the Revenue and Expenditure Budget Reports. The data analysis technique used three value-for-money ratios. The results show that the management of Sidomulyo Village Funds for 2020–2024 is very effective, but still inefficient and economical. This indicates the need to improve expenditure management to optimize it.